Analysis of Multiobjective Scheduling Model for Emergency Management under Multiresource Combination of Disaster Chains - Dan Su; Xiaokang Lei; Yongming Wang; Haijun Wang (Complexity)
This paper analyzes the formation mechanism of urban hazard chains. The results demonstrate that the complex interaction between the disaster-bearing bodies under the action of disaster-causing factors is the direct cause of urban hazard chains. The analysis of the energy effects of urban hazard chains shows that the coupling of the excitation energy released by the causative agent and the energy of the disaster-bearing bodies is the fundamental cause of urban hazard chains. Based on the description of the dynamical mechanism of the urban disaster chain system, this paper first sets up a disaster scenario and considers the effect of the time lag to establish a system dynamics model of the urban disaster chain and urban disaster management. The model of urban disaster management system dynamics shows the mutual influence and complementary relationship between disasters and the economy, pointing out that emphasizing the spill-over effects of disaster management systems can improve the effectiveness of disaster mitigation. This study also uses equilibrium entropy and brittle entropy theories to characterize the vulnerability of single-function networks and the degree of brittle association of each lifeline subsystem, respectively, and establishes a model for assessing the sensitivity of lifeline systems to disaster damage. Built on the collection and feedback of information from disaster areas after the occurrence of emergencies, this paper establishes a deterministic multihazard emergency resource dispatches model and an uncertain multihazard emergency resource dispatch model.